The labor market power of exporting firms: Evidence from Latin America - Francesco Amodio; Emanuele Brancati; Nicolás de Roux; Michele Di Maio (Inter-American Development Bank (IDB), 2024)
Using establishment-level data from the World Bank Enterprise Survey, we assess the market power of exporting firms across 16 countries in Latin America. Leveraging information on export destinations, as well as exchange rate and price data, we construct exchange rate-driven shocks to the marginal revenue product of individual firms. By examining firms' employment and wage responses, we estimate the inverse elasticity of the labor supply they face-a direct indicator of labor market power. In our preferred specification, we estimate that workers employed in exporting firms produce on the margin 83% more than what they earn as wage. We investigate the correlations between labor market power and firm characteristics, country attributes, and labor market institutions and regulations. We find that labor market power is higher for firms in countries where unions, collective bargaining, and unemployment protection are less prevalent.1
Keywords: F10; F14; F16; J2; J3; J42; L10; O54; 330; Firms; Exports; Labor market power; Labor market institutions; Latin America